Pengaruh Akuntansi Hijau, Likuiditas, dan Tanggung Jawab Sosial Perusahaan (CSR) terhadap Keuntungan Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderator - Delia, Ahwai; Fahrul Imam Santoso (UMSurabaya Publishing, 2025)
This research aims to investigate how green accounting variables, liquidity, and corporate social responsibility impact profitability, with company size acting as a moderating variable in firms from the raw material sector listed on the IDX over the period from 2020 to 2023. The sample for the study was selected using a purposive sampling method, resulting in 7 firms being included in the sample. Consequently, the total research sample for the four-year period consisted of 28 observations. To analyze the relationships among the studied variables, multiple regression analysis and moderate regression analysis were conducted using IBM SPSS Statistics 26. The findings of the study reveal that green accounting exerts a negative and insignificant impact on profitability, while liquidity demonstrates a positive yet insignificant influence on profitability, and corporate social responsibility also shows a positive but insignificant effect on profitability. Furthermore, the size of the company does not influence the connection between green accounting and profitability. Additionally, company size does not affect the relationship between liquidity and profitability. However, the findings of the previous research indicate that company size can influence the relationship between corporate social responsibility and profitability.